INSILICO DOCKING STUDIES OF 11-BETA HYDROXYSTEROID DEHYDROGENASE AS A POTENTIAL DRUG TARGET FOR ASTHMA - ARUL JAYAN,; MOHANRAJ,; ANBARASU,; JERRINE JOSEPH, (International Journal of Pharma and Bio Sciences, 2015)
Asthma is a chronic respiratory syndrome. An Insilco study to identify possible drug target for blocking the 11-beta hydroxysteroid dehydrogenase (11-bHSD) enzyme that catalyses the conversion of hydrocortisone to cortisone in the cholesterol metabolism the level of hydrocortisone, which plays a vital role in the control of asthma has been attempted. The inhibition of 11-bHSD by glycyrrhetinic acid, resulted in halting the inflammation in the epithelial cells and ultimately controlling the allergy and Asthma. In this work, we carried out docking studies of the protein 11-bHSD and ligand. Glycyrrhetinic acid, which reveals a better binding of the ligand to the protein. ME Dock, Patch Dock, Hex dock, Gold Dock has been used in this study to reveal the binding. The docking programs successfully works by binding the protein and the ligand gives very useful data about the enzyme values, hydrogen bonds between them, hydrophobic bonds, inter atomic contents between them, and the neighboring amino acids to which the drug has contact. All these studies will give insight in determining the property of the drug.